The (music) educator as producer. Issue 3 (1st December 2018) - King, Andrew
Music technology has been an active part of the Higher Education (HE) curricula for several decades but it is perhaps the last few decades that have witnessed the proliferation of courses at tertiary level, or at least certainly in the United Kingdom. The recently formed Office for Students (OfS) in the United Kingdom replaces HEFCE (Higher Education Funding Council for England) although the remit is somewhat different for this new entity. The OfS is very much a regulator working on behalf of the consumers (students) and not the universities; education is probably the last of the sectors in the United Kingdom to fall into line with this practice since utility and other companies which have had such regulation for years. This brings into sharp focus the view of education as a service industry and the position of education more generally in HE in the United Kingdom. This takes place in the suggested context of a falling number of students engaging with music at schools, sixth form, and further education colleges as a consequence of changes to government policy and the content of the curricula. This article begins by examining music in education and highlighting the current issues. It draws upon recent reports about music in schools before examining the value of music, and especially music technology, in the curriculum. Questions around employability are set out and some key findings from a phenomenological study are presented to educators. Finally, some signposts are set out for future work in this area.